Fraud Auditing - Karyono, Karyono (Journal the Winners: Economics, Business, Management, and Information System Journal, 2002)
Indonesia is recognized as one of the most corrupting countries in the world. That can be seen by the facts that there are so many corruption cases handled by Prosecutor and Police Departments but no one case has been solved properly.Â  Laws and Regulations have been created, controlling, and investigating institutions have been established and maintained but those still cannot touch the corruptors and put them behind bars. Public expects that accountants can improve their professional competences in detecting fraud.Â  This article will overview about fraud auditing, condition causing fraud, characteristics and types of fraud, and the responsibility of auditor in detecting fraud.Â